2017
DOI: 10.1007/5584_2017_114
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Hematopoietic Stem Cell Expansion and Gene Editing Technologies

Abstract: Hematopoietic stem cells (HSCs) are rare cells, which housed in the adult bone marrow. They maintain all types of differentiated blood cells throughout life. Due to limited availability of HSCs for transplantation, treatment of various inherited bone marrow disorders and anemia requires the development of HSC expansion and gene editing technologies. To this end, various studies addressed the use of cytokines and growth factors for HSC expansion. Major hurdle with these studies was found to be spontaneous diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 179 publications
0
20
0
Order By: Relevance
“…HSCs are recognized by their self-renewal and differentiation potential to all blood cell types. They are responsible for generation of billions of mature blood lineages throughout life of an adult 5,34 . HSC transplantation has been used for decades in the treatment of leukemia, lymphoma, some solid cancers, autoimmune diseases and inherited diseases like sickle cell anemia [41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSCs are recognized by their self-renewal and differentiation potential to all blood cell types. They are responsible for generation of billions of mature blood lineages throughout life of an adult 5,34 . HSC transplantation has been used for decades in the treatment of leukemia, lymphoma, some solid cancers, autoimmune diseases and inherited diseases like sickle cell anemia [41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously outlined a number of molecular pathways under regulation of MEIS homeodomain 5,[13][14][15][16][17]27,28,[33][34][35] . We have shown that MEIS1 transcriptionally activate Hif-1α and Hif-2α expression HSCs.…”
Section: Meis Inhibitors Downregulated Meis Target Gene Expressionmentioning
confidence: 99%
“…We have previously outlined a number of molecular pathways under regulation of MEIS homeodomain 5,[13][14][15][16][17]27,28,[33][34][35] . We have shown that MEIS1 transcriptionally activate Hif-1α…”
Section: Meis Inhibitors Downregulated Meis Target Gene Expressionmentioning
confidence: 99%
“…This problem suggests that additional methods and growth factors for expansion of HSCs are required in vitro studies to tackle this limitation. 3,4 It is reported that using frozen HSCs separated from umbilical cord blood (UCB) after 20 years had no negative effect on cell viability and function in HSCs transplant. Although the side effects associated with dimethyl sulfoxide (DMSO) are already recognized, it is still being used as the top standard cryoprotectant in cryoprotection used in UCB banking.…”
Section: Introductionmentioning
confidence: 99%